Prevalência das exodontias em pacientes do distrito de Guaravera, município de Londrina, PR - Lebbos, Samira (Semina: Ciências Exatas e Tecnológicas, 2004)
<!--[if gte mso 9]> Normal 0 21 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--> <!-- /* Font Definitions */ @font-face {font-family:Verdana; panose-1:2 11 6 4 3 5 4 4 2 4; mso-font-charset:0; mso-generic-font-family:swiss; mso-font-pitch:variable; mso-font-signature:536871559 0 0 0 415 0;} /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal {mso-style-parent:""; margin:0pt; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman";} @page Section1 {size:612.0pt 792.0pt; margin:70.85pt 85.05pt 70.85pt 85.05pt; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0;} div.Section1 {page:Section1;} --> <!--[if gte mso 10]> <![endif]--> Statistic investigation of 1.177 entrance form of surgical attendance, in order to verifícate the prevalence of exodontia, making relations the more frequently extracted tooth, in function of the quadrants and individually. The whole number of extractions was 2.408 teeth. The pacient age varied bethween 6 and 76 years old.